2018
DOI: 10.24042/tadris.v3i1.2534
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Learning Module Based on Multiple Representations: The Influence on Students’ Concept Understanding

Abstract: This study aims to describe the effect of using contextual learning module based on multiple representations of static fluid material toward students' conceptual understanding. The sample of this research was the students of class XI IPA 2 and XI IPA 3 in SMA N 1 Trimurjo, Central Lampung. This research was conducted using Pretest-Posttest Control Group Design. Data were tested with N-gain analysis, normality test, homogeneity test and Independent Sample T-test. Results from the Independent Sample T-test value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…This change shows that the learning model is effective in improving student learning outcomes. This is reinforced by previous research [23,24] found that multiple representations can measure students' understanding of concepts through the given tests, while other studies [25,26,27] find that multiple representation learning models can improve learning outcomes and or understanding student concepts. This is because of multiple representations of learning outcomes and knowledge of student concepts by utilizing HOTSbased representations, students can build the idea of circular motion by using the HOTS they have in physics, HOTS of students and the ability of students to describe the results of understanding their concepts in the form of multiple representation are sufficiently honed through the application of this learning model.…”
Section: Table 2 Test the Normality Of Test Results Datamentioning
confidence: 80%
“…This change shows that the learning model is effective in improving student learning outcomes. This is reinforced by previous research [23,24] found that multiple representations can measure students' understanding of concepts through the given tests, while other studies [25,26,27] find that multiple representation learning models can improve learning outcomes and or understanding student concepts. This is because of multiple representations of learning outcomes and knowledge of student concepts by utilizing HOTSbased representations, students can build the idea of circular motion by using the HOTS they have in physics, HOTS of students and the ability of students to describe the results of understanding their concepts in the form of multiple representation are sufficiently honed through the application of this learning model.…”
Section: Table 2 Test the Normality Of Test Results Datamentioning
confidence: 80%
“…Pembelajaran CTL lebih baik untuk meningkatkan keterampilan berpikir kritis siswa (Bustami et.al., 2018). Model CTL juga efektif dalam peningkatan kemampuan pemahaman matematis siswa (Uslima & Rosidin, 2018;Ani et.al., 2017;Merdiana et.al., 2018;Mendrofa, 2020;Sariningsih, 2014). Pendekatan kontekstual (CTL) juga dapat meningkatkan pemahaman dan aplikasi konsep siswa Angket respon terdiri dari 10 pernyataan yang terdiri dari 6 pertanyaan positif dan 4 pernyataan negatif, dengan alternatif jawaban 5 yang dipilih oleh responden yaitu Sangat Setuju (SS), Setuju (S), C (Cukup), Tidak Setuju (TS) dan sangat Tidak Setuju (STS).…”
Section: Pembahasanunclassified
“…Modul sebagai salah satu bahan ajar yang dapat meningkatkan minat dan hasil belajar siswa, buku yang ditulis dengan tujuan agar siswa lebih mandiri dalam hal proses pembelajaran baik ada bimbingan guru maupun tidak. Pembelajaran dengan menggunakan model memudahkan siswa untuk belajar baik dengan guru maupun individu (Uslima, Ertikanto, & Rosidin, 2018). Modul ini berisi semua komponen dasar dari buku teks tersebut.…”
Section: Pendahuluanunclassified